1988
DOI: 10.1152/ajpheart.1988.255.5.h1000
|View full text |Cite
|
Sign up to set email alerts
|

alpha-Adrenoceptors and cold-induced vasoconstriction in human finger skin

Abstract: Experiments were designed to determine how cold-induced vasoconstriction is mediated in superficial vessels of human finger skin. alpha-Adrenoceptor antagonists were administered into the finger skin by iontophoresis, and local cooling was applied by a laser-Doppler probe supplied with Peltier elements. Cold-induced vasoconstriction was abolished after administration of the alpha 2-adrenoceptor antagonist rauwolscine but not after the alpha 1-adrenoceptor antagonist doxazosin. The results indicate that vasocon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
2

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 0 publications
5
78
2
Order By: Relevance
“…Activation of ␣ 1 or ␣ 2 adrenoceptors caused vasoconstriction, but local cooling of the finger enhanced only the vasoconstriction to the ␣ 2 agonist. 37 Similar results were obtained by Freedman and coworkers. 38 More recently, in vitro myograph studies of murine tail arteries indicated that the cold-induced adrenergic contraction was largely due to activation of the ␣ 2c subtype of adrenoceptors.…”
Section: The Distinctive Distribution Of Adrenergic Receptorssupporting
confidence: 83%
“…Activation of ␣ 1 or ␣ 2 adrenoceptors caused vasoconstriction, but local cooling of the finger enhanced only the vasoconstriction to the ␣ 2 agonist. 37 Similar results were obtained by Freedman and coworkers. 38 More recently, in vitro myograph studies of murine tail arteries indicated that the cold-induced adrenergic contraction was largely due to activation of the ␣ 2c subtype of adrenoceptors.…”
Section: The Distinctive Distribution Of Adrenergic Receptorssupporting
confidence: 83%
“…During the first 10 min of local cooling, an immediate and pronounced VC occurs that can be inhibited by either presynaptic sympatholytics or adrenoceptor antagonists (specifically ␣ 2 ) but not with proximal nerve blockade, suggesting a localized (i.e., nonreflex) mechanism dependent on norepinephrine of sympathetic origin binding to ␣ 2 -adrenoceptors (9,12,14,19,24,27,34). The results from the present study help to further clarify the mechanisms underlying this early-phase response to cooling.…”
Section: Discussionmentioning
confidence: 52%
“…fasudil; local cooling; vascular function; adrenergic; norepinephrine CUTANEOUS VASOCONSTRICTION (VC) is the initial thermoregulatory response to defend against cold exposure, effectively minimizing heat loss to the environment. Whole body skin cooling evokes reflex VC, which involves the release of norepinephrine and sympathetic cotransmitters from sympathetic adrenergic axon terminals (38 -40, 42), whereas localized cooling of the cutaneous blood vessels and surrounding tissue engages local (i.e., nonreflex) VC mechanisms that are mediated, in part, by ␣ 2 -adrenoceptors (12,14,27,34). Reflex and local VC are not mutually exclusive responses and often operate in concert during cold exposure to maximize VC (1).…”
mentioning
confidence: 99%
“…9,25 Cold stimulation rapidly increases an endogenous noradrenaline concentration, which, in turn, causes -adrenoceptor-mediated vasoconstriction and a reduction in blood flow. 26 This method is used for the evaluation of autonomic failure, 25,27,28 including Shy-Drager syndrome, Parkinson's disease, amyloidosis and diabetic neuropathy. We demonstrated that 1-adrenoceptor antagonists, which could induce orthostatic hypotension, suppress the finger skin vasoconstrictor response and the degree of the suppression is correlated with the drug plasma concentration.…”
Section: Discussionmentioning
confidence: 99%